2022
DOI: 10.1007/s11356-022-23534-3
|View full text |Cite
|
Sign up to set email alerts
|

The role of effect-based methods to address water quality monitoring in South Africa: a developing country’s struggle

Abstract: Water is an important resource, and it is a worldwide struggle to provide water of good quality to the whole population. Despite good governing laws and guidelines set in place to help protect the water resources and ensure it is of good quality for various consumers, the water quality in South Africa is worsening due to lack of management. The deteriorating infrastructure is becoming progressively worse, due to corruption and insufficient funds. The ever-increasing number of toxicants, as well as the identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Studies reported that, in low and middle-income countries, sewage dispersed into the aquatic environment is not properly treated [59]. This is indeed also the case in South Africa, since municipalities face a number of challenges around providing e cient water services to their residents, mainly due to poor management [39]. This causes poor-quality e uent to be discharged into aquatic systems, including macro-and MPs that harbour potential pathogens in bio lms on their surfaces [1,20,69].…”
Section: Discussionmentioning
confidence: 99%
“…Studies reported that, in low and middle-income countries, sewage dispersed into the aquatic environment is not properly treated [59]. This is indeed also the case in South Africa, since municipalities face a number of challenges around providing e cient water services to their residents, mainly due to poor management [39]. This causes poor-quality e uent to be discharged into aquatic systems, including macro-and MPs that harbour potential pathogens in bio lms on their surfaces [1,20,69].…”
Section: Discussionmentioning
confidence: 99%
“…In relation to water monitoring practices, over the last year these have shifted from quantification practices using analytical techniques such chromatography coupled with mass spectrometry towards effect-based methods, the basis of which involves measuring responses of sentinel species to a compound of interest (e.g., xenobiotic) or even a mixture of chemicals. Effect-based methods capture a particular status of a particular body of water and allow the timely prediction of pollution hot-spots before the damage becomes irreversible [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%